Dynamics of maize grain drying in the high latitude region of Northeast China - Zhen-dong CHU; Bo MING; Lu-lu LI; Jun XUE; Wan-xu ZHANG; Liang-yu HOU; Rui-zhi XIE; Peng HOU; Ke-ru WANG; Shao-kun LI (Journal of Integrative Agriculture, 2022)
A high grain moisture content at harvest has been an important problem in the high latitude region of Northeast China, and it is closely related to the genotypes of varieties, local meteorological factors and planting management. However, delayed harvest at a low temperature could not effectively reduce the grain moisture content. In this study, we continuously observed the grain drying during the late stage of different maturing types of maize varieties in Daqing, Heilongjiang Province, China in 2016 and 2017. A two-segment linear model was used to analyze the different stages of the drying processes: 1) Two-segment linear model fitting can divide the grain drying process of all varieties into two separate linear drying processes with different slopes. 2) During the rapid drying stage, the drying was faster at a higher temperature. The rate of slow drying was influenced by air vapor pressure. 3) The moisture content and meteorological factors when the drying rate turns from one stage into the other were not consistent between varieties and years. After entering the frost period, temperatures below 0°C will significantly reduce the rate of grain drying. 4) Due to the short growth period of early-maturing varieties, the drying time was prolonged, and the grain moisture content was lower than that of the mid-late maturing varieties. Local meteorological conditions do not allow the drying of mid-late maturing varieties to achieve a lower moisture content. When the temperature falls below 0°C, the drying rate of grain decreases markedly. Therefore, one feasible way to solve the problem of high moisture content is to replace the early-maturing varieties and implement the corresponding cultivation techniques.